Numerical modelling of full scale tidal turbines using the actuator disc approach - Abdul Rahman, Anas (The University of Edinburgh, 2018)
In recent years, the actuator disc approach which employs the Reynolds-Averaged Navier-Stokes (RANS) solvers has been extensively applied in wind and tidal energy field to estimate the wake of a horizontal axis turbine. This method is simpler to administer and requires moderate computational resources in modelling a tidal turbines rotor. Nonetheless, the use of actuator disc approximation in predicting the performance of tidal devices has been limited to studies involving an extremely small disc (e.g. rotor diameter of 0.1 meter). The drawback of a small scale actuator disc model is the overestimation of essential parameters such as the mesh density and the resolution of the vertical layers, making them impractical to be replicated in a regional scale model. Hence, this study aims to explore the methodology on implementation of the Three- Dimensional (3D) actuator disc-RANS model in an ocean scale simulation. Additionally, this study also aspires to examine the sensitivity of the applied momentum source term and its validity in representing full-size tidal devices. Nonetheless, before the effectiveness of an actuator disc in a regional model can be tested, tidal flow models for the area of interest needed to be set up first. This was essential for two reasons: (a) to ensure accurate hydrodynamic flow conditions at the deployment site were replicated, (b) to give confidence in the outputs produced by the regional scale actuator disc simulations, since in-situ turbine measurement data from a real deployment site were difficult to source. This research was undertaken in two stages; in the first stage, a numerical model which can simulate the tidal flow conditions of the deployment sites was constructed, and, in the second stage, the actuator disc method which is capable of modelling an array of real scale-sized tidal turbines rotors has been implemented. In the first stage, tidal flow simulations of the Pentland Firth and Orkney Waters (PFOW) were conducted using two distinct open-source software – Telemac3D, which is a finite element based numerical model, and Delft3D, which is a finite difference based model. Detailed methodologies in developing a 3D tidal flow model for the PFOW using both numerical models were presented, where their functionality, as well as limitations were explored. In the calibration and validation processes, both models demonstrated excellent comparison against the measured data. However, Telemac3D was selected for further modelling of the actuator disc considering the model’s capability to perform parallel computing, together with its flexibility to combine both structured and unstructured mesh. In the second stage, to examine the actuator disc’s accuracy in modelling a full size tidal device, the momentum source term was initially applied in an idealised channel study, where the presence of a 20-meter diameter turbine was simulated for both single and array configurations. The following parameters were investigated: (i) size of the unstructured mesh utilised in the computational domain, (ii) variation in disc’s thickness, (iii) resolution of the imposed structured grid to represent turbine’s enclosure, (iv) variation in the vertical layers, and (v) influence of hydrostatic and non-hydrostatic formulations on the models’ outputs. It is to be noted that the turbine’s support structures have not been included in the modelling. The predicted velocities and computed turbulence intensities from the models were compared against laboratory measurement data sourced from literature, where excellent agreement between the model outputs and the data from literature was observed. In essence, these studies highlighted the efficiency and robustness of the applied momentum source term in replicating the wake profiles and turbulence characteristics downstream of the disc, hence providing credence in implementing the actuator disc method for a regional scale application. Subsequently, the validated actuator disc method was applied to the Inner Sound region of the Pentland Firth to simulate arrays of up to 32 tidal turbine rotors. The wake development, flow interactions with the rotor arrays, and flow recovery at the Inner Sound region have been successfully mapped. Also, this study highlighted the importance of employing optimal numerical margins, specifically for the structured grid and horizontal planes, as both parameters were relevant in defining the disc’s swept area. As published materials on the implementation of actuator disc approach within a regional scale model is still scarce, it was aspired that this work could provide some evidence, guidance and examples of suggested best practice in effort to fill the research gap in modelling tidal turbine arrays using the actuator disc approach.
Keywords: tidal energy; actuator disc; renewable energy; three-dimensional; marine